Pencegahan Stunting dengan Pembentukan Tim Pendamping Ibu Hamil - Ratih Nurani Sumardi; Sanya Anda Lusiana; I Rai Ngardita; Flora Niu (Universitas Muhammadiyah Semarang, 2024)
Stunting (short) is still a public health problem in Indonesia. The prevalence of stunting in Papua is still high (29.0%), and in Jayapura City, it is 22.9%. For the Imbi sub-district, stunting is 37%. Efforts to prevent stunting through specific interventions that reduce stunting by 30% and generally in the health sector focus on the First 1000 Days of Life (HPK). Specific intervention targets are pregnant women, breastfeeding mothers, toddlers, and young women. Assistance for pregnant women is needed so that mothers get nutritional intake according to their needs and prepare mothers for feeding their children (IYCF). This activity aims to form a team to accompany pregnant women who will attend mothers to increase their knowledge and practice of maternal nutrition. The method used is training and mentoring. The targets of this activity are Posyandu cadres as an accompanying team and pregnant women in Imbi Village, North Jayapura District. This activity will be carried out from February to August 2023. Results of community service activities: a team of companions for pregnant women was formed at 2 Posyandu in the work area of Imbi Health Center, Imbi Village, consisting of 5 companions at Posyandu Tampandura and three companions at Posyandu Mahikay. There was an increase in cadres' knowledge by 30 points after the training. Mentoring activities were successfully carried out for four months. From these activities, there was an increase in Hb levels, mothers' motivation to carry out ANC examinations, and an increase in the LILA of pregnant women. Conclusion: assistance to pregnant women can overcome maternal nutritional problems and reduce risk factors for stunting children. Suggestion: It is necessary to continue to guide the accompanying team by Health officers for the sustainability of this program.